Negative Theology and Theophany in Dante’s Paradiso - Franke, William (Verbum Vitae, 2023)
Dante’s Paradiso presents a gothic theophany realizing the divine vision (visio Dei) in poetic language. Specifically, Dante’s vision of a line from Scripture (DILIGITE IUSTITIAM QUI IUDICATIS TERRAM) in the Heaven of Jove (Canto XVIII) gives a concrete form of written letters to his vision of God. Yet all that Dante actually sees is only a sign of the invisible, metaphysical reality of God and the supersensible universe of pure being or love. This tension between the sensory plenitude of his vision and the transcendent truth that Dante envisages lends his poem its extraordinary force and attractive power. The paradoxes of negative theology and its inevitable relation with an affirmative theology expressed as poetic vision are worked out with matchless subtlety in Dante’s descriptions and reflections, some of which are expounded in a speculative key in this essay drawn from a more detailed and comprehensive inquiry into the subject. The immediacy of Dante’s vision of letters of Scripture in the Heaven of Jove serves as a metaphor for an unmediated vision of God, but the vision’s content turns out to be nothing other than mediation – concretely, language as the medium mediating his relation to God as Logos. Dante’s vision from beginning to end of the Paradiso is placed under the sign of the ineffability topos, yet what he sees are words and language and ultimately letters. Dramatically displaying the mediations in which language consists becomes itself a metaphorical realization of divine revelation. The mechanisms of signifying in languagemade visibly manifest in writing and specifically as the first line of the Book of Wisdom in Scripture are unveiled as a negatively theological revelation of divinity.